Penguatan Literasi Digital Kritis Generasi Internet melalui Edukasi Internet Sehat di Panti Asuhan Putra Ulil Abshar Kabupaten Malang: Penguatan Literasi Digital Kritis Generasi Internet melalui Edukasi Internet Sehat - Mochammad Alexander Mujiburrohman; Ruth Agnesia Sembiring; Achmad Djunawan (Jurnal Abdimas Jatibara, 2026)
Internet use among adolescents has increased access to information and learning opportunities but has also exposed them to various digital risks, including hoaxes, cyberbullying, plagiarism, harmful content, and unsafe online behavior. The Objectives of this community service program aimed to strengthen critical digital literacy among adolescents at Putra Ulil Abshar Orphanage, Malang Regency, through healthy and safe internet education. Methods of the program was conducted on 7 August 2021 and involved 32 adolescents. Activities included observation, needs assessment, educational sessions, discussions, question-and-answer activities, and reflective evaluation. Participant engagement and understanding were assessed through interactive participation and feedback during the program. The Results program increased participants’ awareness of productive, ethical, and responsible internet use. Participants demonstrated a better understanding of digital risks, including misinformation and unsafe online practices. They were also able to relate the educational content to their daily internet experiences and explain key principles of healthy internet use. Healthy internet education effectively promoted critical digital literacy among adolescents in an orphanage setting. The program provided practical knowledge on digital ethics, online safety, and responsible internet behavior, highlighting its potential as a preventive strategy for fostering safer digital engagement among young people.